2016
DOI: 10.3390/toxins8120373
|View full text |Cite
|
Sign up to set email alerts
|

Limited Link between Oxidative Stress and Ochratoxin A—Induced Renal Injury in an Acute Toxicity Rat Model

Abstract: Ochratoxin A (OTA) displays nephrotoxicity and hepatotoxicity. However, in the acute toxicity rat model, there is no evidence on the relationship between OTA and nephrotoxicity and hepatotoxicity. Based on this, the integrated analysis of physiological status, damage biomarkers, oxidative stress, and DNA damage were performed. After OTA treatment, the body weight decreased and AST, ALP, TP, and BUN levels in serum increased. Hydropic degeneration, swelling, vacuolization, and partial drop occurred in proximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…The detection of ROS in the embryos is therefore a very sensitive method to confirm that OTA is detrimental for zebrafish embryos. Oxidative stress has also been observed in OTA-treated rodents [ 34 , 35 , 36 ], although a link between ROS occurrence and detrimental effects, for example, renal toxicity was found to be low in an additional study on rats [ 37 ]. The mechanism by which OTA is able to increase ROS formation has not been fully explored so far.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of ROS in the embryos is therefore a very sensitive method to confirm that OTA is detrimental for zebrafish embryos. Oxidative stress has also been observed in OTA-treated rodents [ 34 , 35 , 36 ], although a link between ROS occurrence and detrimental effects, for example, renal toxicity was found to be low in an additional study on rats [ 37 ]. The mechanism by which OTA is able to increase ROS formation has not been fully explored so far.…”
Section: Discussionmentioning
confidence: 99%
“…However, until now, the OTA response to differences in species was far from clear [ 26 ]. Various in vivo and in vitro studies have identified several diverse metabolites of OTA in different species that could be the cause of slight differences from animals [ 27 , 28 , 29 ]. Therefore, the present study has been designed to investigate the efficacy of CURC on OTA-induced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used the immunohistochemical marker PCNA to determine the effects of repeated stress on the proliferative capacity of thymocytes. PCNA is a nuclear protein associated with the cell cycle [20]. The positive PCNA signals in the thymus, particularly in the cortical part, were significantly lower in stressed animals compared to the controls.…”
Section: Discussionmentioning
confidence: 98%